2021
DOI: 10.4103/tcmj.tcmj_156_20
|View full text |Cite
|
Sign up to set email alerts
|

Role of social capital and self-efficacy as determinants of stress in pregnancy

Abstract: Objectives: The study investigated the role of social capital, self-efficacy, and depression as determinants of stress during pregnancy. Materials and Methods: In a cross-sectional study, 200 low-risk pregnant women with at least 5 years of education and ages 18 or more were enrolled in public obstetric clinics of Babol University of Medical Sciences. The participants completed four questionnaires including Social Capital, Revised Prenatal Distress Questionnaire (NuPDQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
7
0
2
Order By: Relevance
“…Individuals with higher spirituality can better cope with a stressful life and can have a sense of control as well as greater hope (Vasegh et al., 2012). Individuals with higher spirituality have higher social support and less social anxiety (Faramarzi & Pasha, 2015; Silton et al., 2014). Finally, the spiritual well‐being may improve the healthy behaviours of pregnant women by enhancing the planning‐preparation copings.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with higher spirituality can better cope with a stressful life and can have a sense of control as well as greater hope (Vasegh et al., 2012). Individuals with higher spirituality have higher social support and less social anxiety (Faramarzi & Pasha, 2015; Silton et al., 2014). Finally, the spiritual well‐being may improve the healthy behaviours of pregnant women by enhancing the planning‐preparation copings.…”
Section: Discussionmentioning
confidence: 99%
“…38 Previous studies have shown the effect of social support on pregnancy success, and postpartum health conditions of mothers by helping them maintain better mental health, 39,40 feel less anxious, [41][42][43][44] or reduce stress. 45,46 Pregnant women with lower social support had infants with lower birth weight, 47 poor delivery outcomes, and infants with lower Apgar scores than women with higher social support. 48 Studies have reported the role of social support in the relationship between depression and birth outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Social networks can provide survivors with emotional support (e.g., advice, encouragement, someone to talk to) and tangible supports such as money, housing/shelter, childcare, and transportation, all of which are important for survivors as they implement safety strategies to protect themselves (Fleury‐Steiner et al, 2006; L. Goodman et al, 2005; Riger et al, 2000). The benefits of social capital have been documented in the pregnancy literature as well, with higher maternal social capital associated with fewer depressive symptoms and lower stress levels (Kritsotakis et al, 2013; Pasha et al, 2021).…”
Section: Introductionmentioning
confidence: 99%